THE DEVELOPMENT OF ENTERPRISE ARCHITECTURE BUSINESS CRM AT PT. CAPELLA DINAMIK NUSANTARA WITH EAP METHODOLOGY - Bayu Rianto; Chrismondari; Muhammad Jalil; Muhammad Sandi Rais; Asniati Bindas (JURNAL PERANGKAT LUNAK, 2023)
One of the purposes of implementing the enterprise architecture is to create an alignment between business and information technology for organizational needs, the application of enterprise architecture is inseparable from how does an organization plan and designs the enterprise architecture. In designing enterprise architecture a complete and easy methodology is required. Enterprise Architecture Planning or often abbreviated as EAP is a method used to build information architecture. EAP is a method of data quality planning approach that is oriented to business needs and how the implementation of the architecture is carried out in such a way as to support the business cycle and the achievement of the contents of information systems and organizations.